Management of donor-specific antibodies in lung transplantation - Brandon, William; Dunn, Colin; Bollineni, Srinivas; Joerns, John; Lawrence, Adrian; Mohanka, Manish; Timofte, Irina; Torres, Fernando; Kaza, Vaidehi (Frontiers in Transplantation, 2023)
Development of antibodies against donor human leukocyte antigens poses a challenging problem both for donor selection as well as postoperative graft function in lung transplantation. Frequently, donor-specific antibodies limit the pool of potential donor organs and are associated with antibody-mediated rejection, chronic lung allograft dysfunction, and increased mortality. Optimal management strategies for clearance of DSAs are poorly defined and vary greatly by transplant center; most of the data supporting any particular strategy are limited to small-scale retrospective cohort studies. A typical approach to antibody depletion may involve the use of high-dose steroids, plasma exchange, intravenous immunoglobulin, and possibly other immunomodulators or small-molecule therapies. This review seeks to define the current understanding of the significance of DSAs in lung transplantation and outline the literature supporting strategies for their management.